2017
DOI: 10.1113/jp275050
|View full text |Cite
|
Sign up to set email alerts
|

Omecamtiv mercabil and blebbistatin modulate cardiac contractility by perturbing the regulatory state of the myosin filament

Abstract: Key points Omecamtiv mecarbil and blebbistatin perturb the regulatory state of the thick filament in heart muscle.Omecamtiv mecarbil increases contractility at low levels of activation by stabilizing the ON state of the thick filament.Omecamtiv mecarbil decreases contractility at high levels of activation by disrupting the acto‐myosin ATPase cycle.Blebbistatin reduces contractility by stabilizing the thick filament OFF state and inhibiting acto‐myosin ATPase.Thick filament regulation is a promising target for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
132
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(152 citation statements)
references
References 60 publications
18
132
2
Order By: Relevance
“…Subsequent studies confirmed that OM increases the rate of phosphate release 6,7 ; however, it was also shown that OM inhibits the velocity of actin gliding in the in vitro motility assay at all concentrations tested 6,[8][9][10] and reduces the rate of tension development and relaxation in myocytes at micromolar concentrations 1,9,[11][12][13] . These phenomena, along with observations of decreased isometric force in fully activated cardiomyocytes, 11,14 are inconsistent with the originally proposed model for OM-activation of myosin in muscle.…”
Section: Introductioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Subsequent studies confirmed that OM increases the rate of phosphate release 6,7 ; however, it was also shown that OM inhibits the velocity of actin gliding in the in vitro motility assay at all concentrations tested 6,[8][9][10] and reduces the rate of tension development and relaxation in myocytes at micromolar concentrations 1,9,[11][12][13] . These phenomena, along with observations of decreased isometric force in fully activated cardiomyocytes, 11,14 are inconsistent with the originally proposed model for OM-activation of myosin in muscle.…”
Section: Introductioncontrasting
confidence: 70%
“…We carried out simulations to determine whether the results we observed in the optical trapping assay could explain the effect of OM on the actin gliding rate in the in vitro motility assay 6,8-10 and on the calcium-dependence of contractile function of cardiomyocytes 11,14 . We used a simple, two-state model of the actomyosin cycle along with cooperative activation of the thin filament as simulated by Walcott et al 27,28 (See Online Methods).…”
Section: Calcium Sensitization and Motility Inhibition By Om Is Explamentioning
confidence: 99%
“…The mechanism of action of a cardiac myosin activator, Omecamtiv mecarbil (OM) has been elucidated: OM favors the PPS conformation and thus increases the number of heads able to participate in force production upon the systole on-set 11 . Interestingly, a recent study has concluded that OM is not compatible with the sequestered state of cardiac myosin while the myosin inhibitor blebbistatin (BS) favors the sequestered state 40 . Our results are consistent with this study since the site of blebbistatin is internal and is not affected by IHM contacts.…”
Section: Implications For Future Treatmentsmentioning
confidence: 99%
“…7) will be important in contracting cardiac muscle. Mechanisms likely regulating this transition include RLC phosphorylation [35], myosin-binding protein-C [31], thick-filament mechano-sensing [36], and small molecules [37].…”
Section: Resultsmentioning
confidence: 99%